Numerical Simulation and Dynamic Analysis of Single-Hole Cliff-Side Loess Cave Dwelling under Seismic Actions - Hao, Yane; Liang, Xingwen; Lan, Yongqiang (Geofluids, 2021)
Loess cave dwellings are the most typical style of regional architecture in northwest China; now, there are still tens of millions of people living in them. The northwest is an earthquake-prone area, and cave dwellings have suffered a lot of damage in previous moderate and strong earthquakes, so their earthquake resistance has attracted people’s attention. At present, the seismic analysis of aboveground building structures is relatively mature, while the seismic analysis of loess cave dwellings is less researched. To study the seismic response of loess cave dwellings, a single-hole cliff-side loess cave dwelling located in Yangjialing revolution former sites of Yan’an City of northwest China was investigated and surveyed; the three-dimensional numerical model was established by MIDAS/GTS NX. Combining the historic earthquake damage investigation, dynamic time-history analysis of the single-hole loess cliff-side cave dwelling subject to four horizontal earthquake actions was conducted to determine the weak positions, failure characteristics, and the corresponding displacement and stress of the loess cave dwelling under earthquake load. The results show that the loess has an amplification effect on the seismic waves, the arch vault is a key factor to the stability of the loess cave dwellings, the cliff-side loess cave dwellings in an 8-degree area cannot be used to continue living, and the entrance to loess cave dwellings is the most dangerous place when the earthquake happens.